2015
DOI: 10.1021/acs.est.5b03163
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution in Table Salts from China

Abstract: Microplastics have been found in seas all over the world. We hypothesize that sea salts might contain microplastics, because they are directly supplied by seawater. To test our hypothesis, we collected 15 brands of sea salts, lake salts, and rock/well salts from supermarkets throughout China. The microplastics content was 550-681 particles/kg in sea salts, 43-364 particles/kg in lake salts, and 7-204 particles/kg in rock/well salts. In sea salts, fragments and fibers were the prevalent types of particles compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
404
3
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 854 publications
(427 citation statements)
references
References 30 publications
3
404
3
17
Order By: Relevance
“…The verification of microplastics using a m-FT-IR microscopy followed the method describe by Yang et al (2015). All spectra were compared with a data base (Hummel Polymer and Additives, Polymer Laminate Films, Cross Sections Wizard, HR Specta IR Demo, Aldrich Vapor Phase Sample Library) to verify the individual plastic item.…”
Section: Verification Of Microplastics Using M-ft-ir and Sem/edsmentioning
confidence: 99%
See 3 more Smart Citations
“…The verification of microplastics using a m-FT-IR microscopy followed the method describe by Yang et al (2015). All spectra were compared with a data base (Hummel Polymer and Additives, Polymer Laminate Films, Cross Sections Wizard, HR Specta IR Demo, Aldrich Vapor Phase Sample Library) to verify the individual plastic item.…”
Section: Verification Of Microplastics Using M-ft-ir and Sem/edsmentioning
confidence: 99%
“…Accumulating evidence has suggested that microplastics can bring adverse effects on energy metabolism, immunity and even reproduction of organisms (Wright et al, 2013;Sussarellu et al, 2016;Galloway and Lewis, 2016). Microplastics can also be retained through the food chain and enter human bodies through diverse pathways (Farrell and Nelson, 2013;Seltenrich, 2015;Yang et al, 2015). Therefore, we need to pay close attention to the high levels of microplastic contamination in Taihu Lake and any possible human health risk from consumption of fishery products.…”
Section: Microplastic Pollution Levels and Characteristic In Taihu Lakementioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, organisms able to degrade petrochemical plastics have been described [Wierckx et al, 2015]. One of the biggest concerns is the low degradation rates of these plastics allowing its accumulation in landfills, oceans, among other ecosystems [Chen and Patel, 2012], resulting in problems in harmful solid waste disposal management, likely to penetrate the food chain [Browne et al, 2008;Yang et al, 2015]. One alternative to these materials are the polyhydroxyalkanoates (PHA).…”
Section: Introductionmentioning
confidence: 99%